Factors Influencing Purchase Intention of South Korean Cosmetics and Skincare - Ekklesia Ekklesia; Erilia Kesumahati (Universitas Respati Indonesia, 2023)
This study intends to analyze factors that can influence South Korean cosmetics and skincare purchase intention. This research uses a quantitative research design. A total of 301 samples were collected using the purposive sampling method. The data is processed using IBM SPSS Statistics version 26.0 software and Smart PLS version 3.0. The results obtained from this study are that E-WOM, brand awareness, and brand image have a significant positive effect on purchase intention. Brand ambassador and sender's expertise have no significant effect on purchase intention. E-WOM and brand awareness have a significant positive effect on brand image. E-WOM and brand awareness mediated by brand image has a significant positive effect on purchase intention.